Carotenoid to bacteriochlorophyll energy transfer in the RC-LH1-PufX complex from Rhodobacter sphaeroides containing the extended conjugation keto-carotenoid diketospirilloxanthin - Šlouf, Václav; Keşan, Gürkan; Litvín, Radek; Swainsbury, David J K; Martin, Elizabeth C; Hunter, C Neil; Polívka, Tomáš (Photosynthesis research, 2018)
RC-LH1-PufX complexes from a genetically modified strain of Rhodobacter sphaeroides that accumulates carotenoids with very long conjugation were studied by ultrafast transient absorption spectroscopy. The complexes predominantly bind the carotenoid diketospirilloxanthin, constituting about 75% of the total carotenoids, which has 13 conjugated C=C bonds, and the conjugation is further extended to two terminal keto groups. Excitation of diketospirilloxanthin in the RC-LH1-PufX complex demonstrates fully functional energy transfer from diketospirilloxanthin to BChl a in the LH1 antenna. As for other purple bacterial LH complexes having carotenoids with long conjugation, the main energy transfer route is via the S2-Qx pathway. However, in contrast to LH2 complexes binding diketospirilloxanthin, in RC-LH1-PufX we observe an additional, minor energy transfer pathway associated with the S1 state of diketospirilloxanthin. By comparing the spectral properties of the S1 state of diketospirilloxanthin in solution, in LH2, and in RC-LH1-PufX, we propose that the carotenoid-binding site in RC-LH1-PufX activates the ICT state of diketospirilloxanthin, resulting in the opening of a minor S1/ICT-mediated energy transfer channel.
Keywords: přenos energie; fluorescenční spektrometrie; Energy Transfer; světlosběrné proteinové komplexy; Signal Processing, Computer-Assisted; vysokoúčinná kapalinová chromatografie; Bacteriochlorophylls; karotenoidy; počítačové zpracování signálu; Carotenoids; Light-Harvesting Protein Complexes; Rhodobacter sphaeroides; bakteriochlorofyly; Kinetics; kinetika; Chromatography, High Pressure Liquid; Spectrometry, Fluorescence; Xanthophylls; xanthofyly